Art Systems in Latin America. - ICA (Institute of Contemporary Arts), London; Espace Pierre Cardin, Paris (Buenos Aires : CAYC - Centro de Arte Y Comunicacion., 1974)
Andres, Mauricio ; de Aquino, Angelo ; Barrios, Alvaro ; Bedel, Jacques ; Bercetche, Juan ; Berni, Antonio ; Caraballo, Jorge ; Cordeiro, Waldemar ; Cravo Neto, Mario ; Cugat, Delia ; D'Alessandro, Horacio ; etc.
Art Systems in Latin America, Institute of Contemporary Arts, London ; Nash House, London, December 1974 ; Art de Systèmes en Amérique Latine, Espace Pierre Cardin, Paris, Février-Mars 1975
boek
Keywords: Latijns Amerika